1995
DOI: 10.1074/jbc.270.33.19225
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Peptidyl Substrates as an Aid in Studying the Substrate Specificity of Human Prohormone Convertase PC1 and Human Furin and Designing a Potent Irreversible Inhibitor

Abstract: The substrate specificities of two human prohormone convertases, furin and PC1, were examined with a series of 7-amino-4-methylcoumarinamide (MCA) containing peptidyl substrates. Using acetyl-Arg-Ser-Lys-Arg-MCA as model, P4 Arg substitution by Lys or Orn resulted for furin in a 538- and a 280-fold lower kcat/Km value, but only in a 14- and 18-fold decrease for PC1. Substitution of P3 Ser by either Pro, Glu, or Lys does not modify significantly the kcat/Km value for PC1, whereas furin activity is seriously imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
81
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 43 publications
14
81
0
Order By: Relevance
“…In these studies it was found that only 1 5 2 0 % of prodynorphin was processed at the monobasic site, whereas 80% of the prodynorphin was processed at dibasic sites, suggesting that PC1 prefers processing at dibasic sites within prodynorphin. This is consistent with the data in the present study with shorter fluorescent peptide substrates; PC 1 cleaves peptides that contain basic residues in the P1 and P2 positions more efficiently as compared with the peptides that contain a basic residue only in the PI position (Jean et al, 1995;present study). These results suggest that although PC1 is able to process prodynorphin at monobasic sites, the efficiency of processing at this site is substantially lower than the processing at dibasic sites.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In these studies it was found that only 1 5 2 0 % of prodynorphin was processed at the monobasic site, whereas 80% of the prodynorphin was processed at dibasic sites, suggesting that PC1 prefers processing at dibasic sites within prodynorphin. This is consistent with the data in the present study with shorter fluorescent peptide substrates; PC 1 cleaves peptides that contain basic residues in the P1 and P2 positions more efficiently as compared with the peptides that contain a basic residue only in the PI position (Jean et al, 1995;present study). These results suggest that although PC1 is able to process prodynorphin at monobasic sites, the efficiency of processing at this site is substantially lower than the processing at dibasic sites.…”
Section: Discussionsupporting
confidence: 93%
“…These results suggest that DCE exhibits cleavage site selectivity; this enzyme could be involved in the processing of certain bioactive peptides at sites that require cleavage at type I in addition to cleavage at the type I11 sites. We find that DCE can efficiently process peptides that contain LysLys at the P1 and P2 positions and an Arg at the P4 position; furin and PC1 cannot efficiently process at this site (Jean et al, 1995). Studies with purified PC2 have shown that a Lys-Lys site within the proenkephalin precursor is processed by this enzyme; the efficiency of processing is substantially lower than the efficiency of processing at Lys-Arg sites (Lindberg et al, 1995).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Furin, PC6B, PC7, and PACE-4 assays were performed in 100 mM HEPES pH 7.5, containing 0.5% Triton X-100 and 1 mM CaCl 2 . PC3 assays were performed as described (Jean et al, 1995). Each enzyme preparation was enzymatically pure based on the absence of PC activity in medium from replicate cells infected with wild-type VV (data not shown).…”
Section: Oocyte Injections and Analysis Of Proteinsmentioning
confidence: 99%
“…The critical role of PCs in the proteolytic maturation of multiple proproteins, their implication in various pathologies (1,10,11), and their unidentified specific and/or redundant functions, make them attractive targets for the development of potent and selective inhibitors. The various successful approaches include: active site-directed chloromethyl ketone inhibitors (12,13), reversible peptide-based inhibitors (14 -17), plant derivatives (18), and several engineered variants of protein-based inhibitors that possess a furin-like motif. These include ␣2-macroglobulin (␣2-MF) (19), ␣ 1 -antitrypsin (␣ 1 -AT) Portland (␣ 1 -PDX) (20 -22), proteinase inhibitor 8 (PI8) (23), the turkey ovomucoid third domain (24), and eglin C (25,26).…”
mentioning
confidence: 99%